Autoradiographic localization of (125I-Tyr4)bombesin-binding sites in rat brain - Zarbin, MA (J Neurosci, 1985)
The binding of (125I-Tyr4)bombesin to rat brain slices was investigated. Radiolabeled (Tyr4)bombesin bound with high affinity (Kd = 4 nM) to a single class of sites (Bmax = 130 fmol/mg of protein); the ratio of specific to nonspecific binding was 6/1. Also, pharmacology studies indicated that the C-terminal of bombesin was important for the high affinity binding activity. Autoradiographic studies indicated that the (125I-Tyr4)bombesin-binding sites were discretely distributed in certain gray but not white matter regions of rat brain. Highest grain densities were present in the olfactory bulb and tubercle, nucleus accumbens, suprachiasmatic and periventricular nuclei of the hypothalamus, central medial thalamic nucleus, medial amygdaloid nucleus, hippocampus, dentate gyrus, subiculum, nucleus of the solitary tract, and substantia gelatinosa. Moderate grain densities were present in the parietal cortex, deep layers of the neocortex, rhinal cortex, caudate putamen, stria terminalis, locus ceruleus, parabrachial nucleus, and facial nucleus. Low grain densities were present in the globus pallidus, lateral thalamus, and midbrain. Negligible grain densities were present in the cerebellum, corpus callosum, and all regions treated with 1 microM unlabeled bombesin. The discrete regional distribution of binding suggests that endogenous bombesin-like peptides may function as important regulatory agents in certain brain loci.